Effect of Target Realization, Absenteeism and Projects on Employee Perfomance of PT Asri Jaya Putra Perkasa - Hartanto, Tomy Dwi (International Journal of Review Management Business and Entrepreneurship (RMBE), 2022)
This study aims to analyze the effect of target realization, absenteeism, and projects on employee performance of PT Asri Jaya Putra Perkasa. This study used target realization (X 1 ), absenteeism (X 2 ), project (X 3 ) as independent variables, and employee performance (Y) as dependent variable. Target realization has aprinciple as indicators based on accuracy, timeliness, and cost accuracy. Absenteeism used 4 indicators, there are attendance, punctuality of arrival, punctuality and attendance outside working hours. In a constructionindustry project there is a PMBOK 2017 standard as a guide containing a collection of knowledge needed by professionals in project management and has 9 main coverage areas that were adapted as indicators for measuring project variables (X 3 ). In measuring the employee performance variable (Y), this study used theory of Bernadin, Russell and Gomez. The population in this study were all employees of PT Asri Jaya Putra Perkasa, totaling 65 respondents, so the sampling method is census method. The analytical tool used is multiple linear regression analysis. The results showed that target realization, absenteeism and project had a significant simultaneous and partial effect on employee performance of PT Asri Jaya Putra Perkasa with the absenteeism having a non-unidirectional effect on employee performance.